2015
DOI: 10.1515/johh-2015-0041
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved oxygen and water temperature dynamics in lowland rivers over various timescales

Abstract: Abstract:The impact of floodplain hydrology on the in-stream dissolved oxygen dynamics and the relation between dissolved oxygen and water temperature are investigated. This has been done by examining the time series of dissolved oxygen and water temperature coupled with meteorological and hydrological data obtained from two lowland rivers having contrasting hydrological settings. Spectral analysis of long-term oxygen variations in a vegetated river revealed a distinct scaling regime with slope '-1' indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 52 publications
(53 reference statements)
4
63
0
3
Order By: Relevance
“…This pattern is further supported by the strong, significant negative relationship between DO concentrations and stream water temperature (r = −0.96, p < 0.0001), which highlights the temperature dependence of diel DO dynamics (Nimick et al, 2011). Such a relationship is consistent with small, shallow and impoverished streams (Rajwa-Kuligiewicz et al, 2015). The night-time maxima and daytime minima in DO observed in the SPR are also found in oligotrophic mountain streams with steep gradients (Nimick et al, 2011).…”
Section: Diel Cyclessupporting
confidence: 57%
“…This pattern is further supported by the strong, significant negative relationship between DO concentrations and stream water temperature (r = −0.96, p < 0.0001), which highlights the temperature dependence of diel DO dynamics (Nimick et al, 2011). Such a relationship is consistent with small, shallow and impoverished streams (Rajwa-Kuligiewicz et al, 2015). The night-time maxima and daytime minima in DO observed in the SPR are also found in oligotrophic mountain streams with steep gradients (Nimick et al, 2011).…”
Section: Diel Cyclessupporting
confidence: 57%
“…As reported by Rajwa-Kuligiewicz et al (2015) Fourier analysis of dissolved oxygen and water temperature time series indicated the existence of one peak in the power spectrum, which corresponds to the daily cycle. Moreover, power spectra of DO, water temperature, and water level time series can be roughly approximated by the "-1" slope.…”
Section: Fourier Power Spectrummentioning
confidence: 56%
“…Moreover, small individual peaks are visible at the period of one week. In fact, this consistency has not been reported in the ear-lier work of Rajwa-Kuligiewicz et al (2015) since both, the statistical method and Fourier technique, failed to show that. Interestingly, high coherence occurs during flood events, suggesting that extreme events such as floods directly affect the river ecosystems.…”
Section: Wavelet Coherence Of Dissolved Oxygen and Water Temperaturementioning
confidence: 82%
See 1 more Smart Citation
“…It is hardly surprising that unsteady flows are intertwined with hysteretic behaviour as observed with respect to many variables (see e.g. O'Kane, 2005;Rajwa-Kuligiewicz et al, 2015;Rowiński et al, 2000). Mao (2012) reported a clockwise hysteresis in experimental tests and attributed this type of relation to changes in organization of bed surface grains, which caused smaller bedload transport along the falling limb.…”
Section: Introductionmentioning
confidence: 99%